Food–bacteria interplay: pathometabolism of emetic Bacillus cereus - Ehling-Schulz, Monika; Frenzel, Elrike; Gohar, Michel (Frontiers in Microbiology, 2015)
Bacillus cereus is a gram-positive endospore forming bacterium known for its wide spectrum of phenotypic traits, enabling it to occupy diverse ecological niches. Although the population structure of B. cereus is highly dynamic and rather panmictic, production of the emetic B. cereus toxin cereulide is restricted to strains with specific genotypic traits, associated with distinct environmental habitats. Cereulide is an ionophoric dodecadepsipeptide that is produced non-ribosomally by an enzyme complex with an unusual modular structure, named cereulide synthetase (Ces NRPS). The ces gene locus is encoded on a mega virulence plasmid related to the Bacillus anthracis toxin plasmid pXO1. Cereulide, a highly thermo- and pH- resistant molecule, is preformed in food, evokes vomiting a few hours after ingestion and was shown to be the direct cause of gastroenteritis symptoms; occasionally it is implicated in severe clinical manifestations including acute liver failures. Control of toxin gene expression in emetic Bacillus cereus involves central transcriptional regulators, such as CodY and AbrB, thereby inextricably linking toxin gene expression to life cycle phases and specific conditions, such as the nutrient supply encountered in food matrices. While in recent years considerable progress has been made in the molecular and biochemical characterization of cereulide toxin synthesis, far less is known about the embedment of toxin synthesis in the life cycle of B. cereus. Information about signals acting on toxin production in the food environment is literally lacking. We summarize the data available on the complex regulatory network controlling cereulide toxin synthesis, discuss the role of intrinsic and extrinsic factors acting on toxin biosynthesis in emetic B. cereus and stress how unraveling these processes can lead to the development of novel effective strategies to prevent toxin synthesis in the food production and processing chain.